PANTHEISM, PANENTHEISM, AND ECOSOPHY: GETTING BACK TO SPINOZA?. Issue 3 (19th May 2022) - Valera, Luca; Vidal, Gabriel
Abstract: Many authors in the field of Environmental Philosophy have claimed to be inspired by Spinoza's monism, which has traditionally been considered a form of pantheism because nature and God coincide. This idea has deep normative implications, as some environmental ethicists claim that wounding nature is the same as wounding God, which implies a resacralization of nature. In particular, we will focus on Arne Næss's Ecosophy (or Deep Ecology) to offer a current relevant example of the pantheist (or panentheist) worldview. However, a new demarcation distinguishes pantheism from panentheism; in the latter, nature and God belong together but do not fully coincide, as in pantheism. Nevertheless, whether Spinoza is a panentheist, pantheist, or neither has yet to be fully determined, as well as whether his doctrine serves as a proper foundation for an ecology that attempts the aforementioned resacralization of nature. This article attempts to clarify these issues.